Pro-organic radical contrast agents ("pro-ORCAs") for real-time MRI of pro-drug activation in biological systems. Issue 29 (8th July 2020) - Nguyen, Hung V.-T.; Detappe, Alexandre; Harvey, Peter; Gallagher, Nolan; Mathieu, Clelia; Agius, Michael P.; Zavidij, Oksana; Wang, Wencong; Jiang, Yivan; Rajca, Andrzej; Jasanoff, Alan; Ghobrial, Irene M.; et al.
Abstract : Pro-organic radical contrast agents (pro-ORCAs) that enable real-time monitoring of doxorubicin prodrug activation in vitro and in vivo are prepared through brush-first ring-opening metathesis polymerization (ROMP). Abstract : Nitroxide-based organic-radical contrast agents (ORCAs) are promising as safe next-generation magnetic resonance imaging (MRI) tools. Nevertheless, stimuli-responsive ORCAs that enable MRI monitoring of prodrug activation have not been reported; such systems could open new avenues for prodrug validation and image-guided drug delivery. Here, we introduce a novel "pro-ORCA" concept that addresses this challenge. By covalent conjugation of nitroxides and drug molecules (doxorubicin, DOX) to the same brush-arm star polymer (BASP) through chemically identical cleavable linkers, we demonstrate that pro-ORCA and prodrug activation, i.e., ORCA and DOX release, leads to significant changes in MRI contrast that correlate with cytotoxicity. This approach is shown to be general for a range of commonly used linker cleavage mechanisms ( e.g., photolysis and hydrolysis) and release rates. Pro-ORCAs could find applications as research tools or clinically viable "reporter theranostics" for in vitro and in vivo MRI-correlated prodrug activation.